Customer Perception towards General Insurance in Kathmandu Valley - Thapa, Shristi (Nepalese Journal of Finance, 2025)
This study examines the customer’s perception towards general insurance in Kathmandu Valley. Customer perception is the dependent variable. The selected independent variables are pricing policy, policy transparency, service delivery process, social influence, and organizational reputation. The primary source of data is used to assess the opinions of respondents regarding pricing policy, policy transparency, service delivery process, social influence, and organizational reputation. The study is based on primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of pricing policy, policy transparency, service delivery process, social influence, and organizational reputation on consumer perception. The study shows that pricing policy is positively correlated to consumer perception. It indicates that affordable pricing policy leads to increase in consumer perception. Likewise, policy transparency is positively correlated to consumer perception. It indicates that better policy transparency leads to increase in consumer perception. Similarly, service delivery system is positively correlated to consumer perception. It indicates that faster the service delivery process, higher would be the consumer perception. Likewise, social influence is also positively correlated to consumer perception. It indicates that higher the social influence, higher would be the consumer perception. Further, organizational reputation is positively correlated to consumer perception. It indicates that positive organizational reputation leads to increase in consumer perception.